2018
DOI: 10.1002/asia.201800970
|View full text |Cite
|
Sign up to set email alerts
|

β‐Cyclodextrin Functionalized Nanoporous Graphene Oxides for Efficient Resolution of Asparagine Enantiomers

Abstract: Efficient resolution of racemic mixture has long been an attractive but challenging subject since Pasteur separated tartrate enantiomers in 19 century. Graphene oxide (GO) could be flexibly functionalized by using a variety of chiral host molecules and therefore, was expected to show excellent enantioselective resolution performance. However, this combination with efficient enantioselective resolution capability has been scarcely demonstrated. Here, nanoporous graphene oxides were produced and then covalently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…The FTIR spectrum of SGO (curve b) shows the stretching vibration of −OH (at 3452 cm −1 ) and CC bond of the benzene ring (at 1633 cm −1 ) as well as C−O−OH on the carboxylic acid (at 1391 cm −1 ) and asymmetrical stretching of C−O−C (at 1150 cm −1 ). 42 It is observed that SGO-NH 2 -βCD (curve c) has characteristic peaks of amide groups in which the peaks at 1631 and 1380 cm −1 correspond to the stretching vibration of CO and C−N from −NHCO−, respectively. 43 The results indicated the successful amidation of SGO with NH 2 -βCD.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The FTIR spectrum of SGO (curve b) shows the stretching vibration of −OH (at 3452 cm −1 ) and CC bond of the benzene ring (at 1633 cm −1 ) as well as C−O−OH on the carboxylic acid (at 1391 cm −1 ) and asymmetrical stretching of C−O−C (at 1150 cm −1 ). 42 It is observed that SGO-NH 2 -βCD (curve c) has characteristic peaks of amide groups in which the peaks at 1631 and 1380 cm −1 correspond to the stretching vibration of CO and C−N from −NHCO−, respectively. 43 The results indicated the successful amidation of SGO with NH 2 -βCD.…”
Section: Resultsmentioning
confidence: 95%
“…For the FTIR spectrum of NH 2 -βCD (curve a), the characteristic absorption peaks at 3442, 2927, 1638, 1156, and 1032 cm –1 could be attributed to the stretching vibrations of −OH/–NH 2 , stretching vibration of −CH 2 , bending vibration of N–H from −NH 2 , stretching vibration of C–O, and asymmetric stretching vibration of the C–O–C group of epoxy group, respectively. The FTIR spectrum of SGO (curve b) shows the stretching vibration of −OH (at 3452 cm –1 ) and CC bond of the benzene ring (at 1633 cm –1 ) as well as C–O–OH on the carboxylic acid (at 1391 cm –1 ) and asymmetrical stretching of C–O–C (at 1150 cm –1 ) . It is observed that SGO-NH 2 -βCD (curve c) has characteristic peaks of amide groups in which the peaks at 1631 and 1380 cm –1 correspond to the stretching vibration of CO and C–N from −NHCO–, respectively .…”
Section: Resultsmentioning
confidence: 99%
“…Cyclodextrins, frequently used in the form of α ‐, β ‐, and γ ‐cyclodextrins ( α ‐CD, β ‐CD, and γ ‐CD, respectively [ 81 ] ), constitute another prevalent category of chiral sources for chiral functionalization of both graphene and GO. Nonetheless, obviously different from amino acids, cyclodextrins are incorporated with graphene and the derivatives much more through noncovalent interactions [ 82–86 ] rather than covalent bonding, [ 87–89 ] probably because of the relatively more difficulties in accomplishing reactions between cyclodextrins and graphene. Another reason may lie in the fact that substitution of the initial OH groups on cyclodextrins may exert influence on their enantioselectivity and the ability to form inclusion complex with guest compounds.…”
Section: Construction Of Chiral Graphene Hybrid Materialsmentioning
confidence: 99%
“…The resulting electrode could recognize tryptophan enantiomers. [ 86 ] Other chiral hybrids exploited following the similar idea are RGO/ β ‐CD/CPE (carbon paste electrode) for electrochemically sensing moxifloxacin hydrochloride enantiomers; [ 97 ] RGO/ β ‐CD/MB/GCE (MB, methylene blue) for electrochemically sensing chiral carboxylic acids; [ 98 ] RGO/ β ‐CD for electrically and optically sensing tryptophan enantiomers; [ 87 ] RGO/PNP/ β ‐CD/CPE (PNP, platinum nanoparticles) for electrochemically sensing chiral clopidogrels; [ 99 ] RGO/PTCA/ β ‐CD (PTCA, 3,4,9,10‐perylene tetracarboxylic acid) for electrochemically recognizing chiral phenylalanine; [ 100 ] RGO/ferrocene/ β ‐CD for electrochemically recognizing phenylalanine racemate. [ 101 ] These studies evidently show the importance of electrochemical sensors for enantio‐differentiating chiral compounds, due to their merits particularly in easy and fast operation.…”
Section: Construction Of Chiral Graphene Hybrid Materialsmentioning
confidence: 99%
See 1 more Smart Citation